PENATALAKSANAAN PEMERIKSAAN RADIOGRAPHY THORAX DENGAN KLINIS EFUSI PLEURA DIINSTALASI RADIOLOGI RSU SUNDARI - ARDIANTA, JONAS (JURNAL ILMIAH SIMANTEK, 2021)
One of the clinical conditions in the thorax is pleural effusion, which is an abnormal accumulation of pleural fluid caused by the formation of pleural fluid faster than the absorption process. Technique. The aim of this study was to determine the thorax examination procedure in clinical pleural effusion at the Radiology Installation of Sundari General Hospital. This type of research is qualitative using a descriptive method, a case study approach. Data collection methods are, observation, interviews, and documentation. From the results of the research, the management of thorax examination in clinical pleural effusion at the Radiology Installation at Sundari General Hospital, thorax examination in clinical pleural effusion requires the patient to be in an erect or standing position. According to the interview results that have been obtained, chest examination in clinical pleural effusion in the PA and lateral positions can confirm the diagnosis of clinical pleural effusion.